Is There a 'New Consensus' on Inequality? - Francisco H. G. Ferreira (Institute of Labor Economics (IZA), 2023)
Thirty years after the "Washington Consensus", is there a new policy consensus that addresses the problem of inequality? This paper argues that there is widespread acceptance that multiple, interrelated and mutually reinforcing inequalities exist – in income, wealth, education, health, power, and recognition – and that these inequalities are generally "too high". There has also been a significant shift towards a shared view that these inequalities matter, both intrinsically and because of their instrumental effects on economic efficiency and political institutions. There is much less consensus, perhaps surprisingly, on what the actual levels of income inequality are, and there are common misperceptions about their trends. In policy terms, there is something approaching a consensus regarding the desirability of various "pre-distribution" policies, ranging from early childhood development to investment in better teaching. In certain quarters, there is also agreement that sharper antitrust regulation, freer labor unions, and more progressive taxation is needed in most countries. But much less is known about how to provide the poor with genuine opportunities to break the cycle of intergenerational transmission of disadvantage in a durable way.
Keywords: D31; D63; H20; 330; inequality; redistribution; policy consensus